ANALISIS KOMPETENSI PEDAGOGIS GURU DALAM MENINGKATKAN KETERAMPILAN MATEMATIS SISWA - Supratman, Moh.; Rahmawati, Helmi; Solihah, Fatimatus (Jurusan Pendidikan Matematika Universitas Borneo Tarakan, 2023)
The aim of this research is to explain how teachers acquire teaching skills to develop students' mathematical competence. The research method used is literature study. This research was conducted using a systematic literature review (SLR) approach. The data collection instrument was an article, carried out using the Publish Or Perish (POP) application then entered into Google Schoolar with the keyword